East Ends: race, place and community in the story of the emergence of Grime music - Pickering, Joshua Osoro (2019)
This thesis tells the story of the emergence of Grime music. Grime, as a music sub-culture has its origins in the Caribbean community of East London, at the turn of the twenty-first century and can be seen as a continuation of the lineage of Caribbean and Caribbean-British music genres that also takes in influences from other parts of the world. I will be describing the story of Grime from a particular angle: that which considers the racial prejudice, and cultural suppression faced by London’s black communities in the period before Grime’s emergence, as well as during it, and the effects of economic gentrification in the area. I will demonstrate that a combination of British racism and local gentrification were responsible for Grime being pushed out of its traditional communities. I will support this, despite a paucity of academic texts, by drawing on a vast wealth of online resources that followed Grime’s forced transition from the physical environment of East London to the digital world. I will also argue that this transition, though an unintentional effect of suppression, is the cause behind Grime’s rise to becoming a mainstream culture that now represents Britain’s wider working-class black and ethnic minority community while maintaining its street authenticity: its life-source and central ethos.